In Situ Growth and Characterization of Metal Oxide Nanoparticles within Polyelectrolyte Membranes. (19th August 2016) - Landers, John; Colon‐Ortiz, Jonathan; Zong, Kenneth; Goswami, Anandarup; Asefa, Tewodros; Vishnyakov, Aleksey; Neimark, Alexander V.
Abstract: This study describes a novel approach for the in situ synthesis of metal oxide–polyelectrolyte nanocomposites formed via impregnation of hydrated polyelectrolyte films with binary water/alcohol solutions of metal salts and consecutive reactions that convert metal cations into oxide nanoparticles embedded within the polymer matrix. The method is demonstrated drawing on the example of Nafion membranes and a variety of metal oxides with an emphasis placed on zinc oxide. The in situ formation of nanoparticles is controlled by changing the solvent composition and conditions of synthesis that for the first time allows one to tailor not only the size, but also the nanoparticle shape, giving a preference to growth of a particular crystal facet. The high‐resolution TEM, SEM/EDX, UV‐vis and XRD studies confirmed the homogeneous distribution of crystalline nanoparticles of circa 4 nm and their aggregates of 10–20 nm. The produced nanocomposite films are flexible, mechanically robust and have a potential to be employed in sensing, optoelectronics and catalysis.